Clara Cell Protein Expression in Mechanically Ventilated Term and Preterm Infants with Respiratory Distress Syndrome and at Risk of Bronchopulmonary Dysplasia: A Pilot Study. (11th April 2017) - Guzmán-Bárcenas, José; Calderón-Moore, Antonio; Baptista-González, Héctor; Irles, Claudine
Abstract : The aim of this pilot study was to determine Clara cell protein (CC16) concentration in bronchoalveolar lavages (BAL) fluid from full-term and preterm (<37 weeks' gestational age) neonates requiring respiratory support, having symptoms of neonatal respiratory distress syndrome, and at risk of bronchopulmonary dysplasia (BPD). We hypothesized that CC16 may be predictive of BPD diagnosis regardless of gestational age. BAL fluid CC16 was measured by ELISA at birth and at day 7 of life. Both groups that developed BPD showed significantly decreased BAL fluid CC16 levels compared to those infants that did not develop the disease. CC16 positively correlated with diagnosis of BPD and negatively with the severity of the disease. These results suggest that BAL fluid CC16 levels may have a diagnostic value at day 7 for BPD in both term and preterm infants. This study demonstrates the potential utility of BAL fluid CC16 levels as a biomarker for BPD in term infants.